Reward prospect affects strategic adjustments in stop signal task - Giuffrida, Valentina; Marc, Isabel Beatrice; Ramawat, Surabhi; Fontana, Roberto; Fiori, Lorenzo; Bardella, Giampiero; Fagioli, Sabrina; Ferraina, Stefano; Brunamonti, Emiliano; Pani, Pierpaolo (Frontiers in Psychology, 2023)
Interaction with the environment requires us to predict the potential reward that will follow our choices. Rewards change depending on the context and our behavior adapts accordingly. However, in real life, organisms must adapt to ever-changing contexts in which continuous adaptation between the two options is required. Previous studies have shown that, depending on reward regimes, actions can be facilitated (i.e., increasing the reward for response) or interfered (i.e., increasing the reward for suppression). Here we studied how the change in reward perspective can influence subjects' adaptation strategy. Students were asked to perform a modified version of the Stop-Signal task. Specifically, at the beginning of each trial, a Cue Signal informed subjects of the value of the reward they would receive; in one condition, Go Trials were rewarded more than Stop Trials, in another, Stop Trials were rewarded more than Go Trials, and in the last, both trials were rewarded equally. Subjects participated in a virtual competition, and the reward consisted of points to be earned to climb the leaderboard and win (as in a video game contest). The sum of points earned was updated with each trial. After a learning phase in which the three conditions were presented separately, each subject performed 600 trials testing phase in which the three conditions were randomly mixed. Based on the previous studies, we hypothesized that subjects could employ different strategies to perform the task, including modulating inhibition efficiency, adjusting response speed, or employing a constant behavior across contexts. We found that to perform the task, subjects preferentially employed a strategy-related speed of response adjustment, while the duration of the inhibition process did not change significantly across the conditions. The investigation of strategic motor adjustments to reward’s prospect is relevant not only to understanding how action control is typically regulated, but also to work on various groups of patients who exhibit cognitive control deficits, suggesting that the ability to inhibit can be modulated by employing reward prospects as motivational factors.